Training of Caregiver Towards Family Independence Level in Caring for Elderly With Hypertension - Mona Meylinda Sari; Syahrul Syahrul; Silvia Malasari (Indonesian Contemporary Nursing Journal, 2016)
Introduction: Knowledge and understanding of  care of families will have an impact on their attitudes and behavior in delivering care to elderly’s daily activities. By using knowledge, the family will take right attitude in caring elderly to achieve the optimal health. This study aims determine the effect of caregiver’s training to the independence level of family in caring elderly with hypertension.Method: This study used a pre experimental one group pre test post test design. The instrument was used a questionnaire and observational sheet. Sample in this study were 35 people. The test used was alternative wilcoxon test with the significance α=0.05.Result: The result was obtained that before training, all of caregivers, 35 (100 %)  at a level of independence rate I. After training, 8 (23 %) at a level of independence rate I, 8 (23 %) at a level of independence rate II, 6 (17 %) at a level of independence rate III, 13 (37.1 %) at a level of independence rate IV. There are significant effect of the independence of caregiver after training (p=0.000).Conclusion: There are also significant effect of the knowledege and skill of caregiver after training. This study recommends a further study to observe motivation of caregiver in changing their attitudes of caring to elderly.